Electrical performance of polymer-insulated rail brackets of dc transit subjected to lightning induced overvoltage - Rahman F.A.A.; Kadir M.Z.A.A.; Amirulddin U.A.U.; Osman M. (MDPI AG, 2023)
Electrolysis; Glass fibers; Light rail transit; Lightning; Pultrusion; Reinforced plastics; Sensitivity analysis; Surge protection; Cycloaliphatic epoxies; Electrical performance; Energy absorption capacity; Glass reinforced plastics; Induced over voltages; Lightning induced overvoltage; Performance comparison; Railway electrifications; Electric railroads